A comparison study between wide‐range and high‐sensitivity C‐reactive protein assays (Roche Cobas c702) for low C‐reactive protein concentration in patients with cardiovascular risk. Issue 8 (20th June 2019) - Li, Runqing; Xue, Yajun; Wang, Tengjiao; Gong, Lijun; Peng, Peng; Xiong, Pan; Dai, Mingzhu; Shao, Tongju; Hu, Yuhan; Ye, Xinchen
Abstract: Background: Low concentration C‐reactive protein (CRP) has favorable prognostic significance in patients with cardiovascular risks. Methods: We compared the wr‐CRP method with the hs‐CRP method both on Roche Cobas c702 analyzer for the determination of low CRP concentration (<20 mg/L) including 200 patients treated in Cardiology Department in Beijing Tsinghua Changgung Hospital (Beijing, China) from December 2018 to March 2019. Results: The two methods were highly correlated (Spearman's rho = 0.995). Deming regression was used to fit the regression analysis model, giving a slope of 1.058 with an intercept of 0.008. The median method difference (wr‐CRP − hr‐CRP) was 0.120 mg/L (95% CI, 0.086‐0.200 mg/L), and the median percent differences were 7.34% (95% CI, 4.27%‐8.47%). The percent bias between both methods at the given cutoff CRP values of 1, 3, and 10 mg/L evaluated by Deming regression was 6.60%, 6.07%, and 5.88%, respectively, all of which were less than the acceptable standard (12.50%). The percentage of sample results concordant by both methods for the risk stratification was 96.0% ( kappa = 0.937, P < 0.001). Conclusions: Roche wr‐CRP and hs‐CRP assays are highly concordant in determining low concentration CRP. Wr‐CRP may be used as an alternative to hs‐CRP assay on Roche Cobas c702 analyzer to assess the cardiovascular risk, considering its convenience and lower costs.